Real-world outcomes for the treatment of relapsed/refractory multiple myeloma patients with lenalidomide-dexamethasone combinations in a Latin American country. A retrospective cohort study from grupo argentino de mieloma múltiple. Issue 3 (4th March 2021) - Duarte, Patricio Jose; Schutz, Natalia Paola; Ochoa, Paola; Yantorno, Sebastian; Orlando, Sergio; Lopresti, Sergio; Zabaljauregui, Soledad; Aizpurua, Florencia; Shanley, Claudia; Giannini, Elvira; Garate, Gonzalo; Foncuberta, Cecilia; et al.
ABSTRACT: Objectives: We compared the efficacy of lenalidomide-dexamethasone (Rd) based treatments for relapsed/refractory multiple myeloma patients (pts), in a real-world setting. In addition, we evaluated adverse events (AE), progression-free survival (PFS) and overall survival (OS). Methods: In our retrospective, multicentric study, 156 pts with RRMM were included. 74/156 pts (47%) were refractory to bortezomib (V) and 43/156 (27%) pts to lenalidomide (R), with 24/156 (15%) of pts double refractory. Eighty-six pts (55%) received Rd with carfilzomib (KRd), 30 pts (19%) bortezomib (VRd), 30 pts (19%) daratumumab (DRd), and 10 pts (6%) ixazomib (IRd). Results: The overall response (ORR) (≥ partial response) for the entire cohort was 71%, with a very good partial response rate or better (≥VGPR) of 35%. We found no significant differences in CR or ≥VGRP rates between treatments (p:0.229). Regardless of the combination received, those patients who achieved CR had significantly improved PFS (p: 0.007). The most frequent cause of treatment discontinuation was disease progression in 55/156 pts (35%). 8 pts (5%) discontinued treatment due to treatment-related adverse events (AE). Conclusion: This is the first report of Rd combinations for the treatment of RRMM in Latin America. All combinations proved to be effective with an acceptable toxicity.